UTILIZATION OF CORN AND PEANUT HARVESTS FOR THE DEVELOPMENT OF SUPERIOR FOOD PRODUCTS - Suryani, Lely; Fatima, Imaculata; Mutiara, Charly; Fowo, Krisnoto Yohanes; Rinda, Regina Caely Jessy; Djina, Novita Nia Leo; Nae, Yohanes Debrito; Blolon, Godeliva Doi; Peti, Maria Vianey; Punan, Yanuarius; Wolo, Rodriques Da Weo (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Tendambonggi village has considerable agricultural potential, particularly in corn and peanuts. However, most farmers still use conventional methods, rely on a single crop, and lack the skills to manage their harvest into value-added products. This situation has resulted in agricultural production not being able to contribute optimally to improving the community’s economy. This program aims to utilize corn and peanut harvests as raw materials for the development of superior food products through training and assistance based on local innovation. Implementation methods include socialization activities, training in the manufacture of processing products such as corn tempeh, corn flour, and corn noodles, as well as training in the processing of fried peanuts as a food product unique to Tendambonggi Village. In addition, the program also integrates an agroecological approach through the use of natural organic fertilizers to improve soil fertility and reduce dependence on chemical fertilizers. The results show an increase in the community’s skills in processing crops into food products that are competitive in the market, as well as a growing awareness of the importance of innovation and agricultural sustainability. This activity is expected to encourage the formation of joint business units that manage corn and peanut processing independently and sustainably, while strengthening food security and the local economy in Tendambonggi Village.